The Relationship Between the Duration of Use Of 1-Month Contraceptive Injections and the Menstrual Cycle in Long-Term Acceptors at TPMB Maya - Chairun Nisa; Widia Shofa Ilmiah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Menstrual cycle disturbances are common side effects of injectable hormonal contraception and may affect contraceptive satisfaction and continuation. This study aimed to analyze the relationship between the duration of injectable contraceptive use and menstrual cycle disturbances among injectable contraceptive acceptors. A quantitative analytic study with a cross-sectional design was conducted at TPMB Maya from September to October 2025. A total of 67 injectable contraceptive users were included using a total sampling technique. The independent variable was the duration of injectable contraceptive use, categorized as less than one year and more than one year, while the dependent variable was menstrual cycle disturbance. Data were collected using a structured questionnaire and analyzed through univariate analysis and Kendall’s tau-b correlation test. The results showed that most respondents were aged 20–35 years (86.6%), had a senior high school education (55.2%), and were multiparous (77.6%). Most respondents had used injectable contraception for more than one year (82.1%), and 74.6% experienced menstrual cycle disturbances. Bivariate analysis revealed a statistically significant relationship between the duration of injectable contraceptive use and menstrual cycle disturbances (τ = −0.264; p = 0.032). The study concludes that longer use of injectable contraception is associated with a higher occurrence of menstrual cycle disturbances, emphasizing the importance of duration-based counseling in family planning services.